2013
DOI: 10.1007/s11095-013-1116-2
|View full text |Cite
|
Sign up to set email alerts
|

Altered Brain Uptake of Therapeutics in a Triple Transgenic Mouse Model of Alzheimer’s Disease

Abstract: These studies systematically assessed the impact of AD on BBB drug transport in a relevant animal model, and have demonstrated a reduction in the brain uptake of passively-absorbed molecules in this mouse model of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 44 publications
5
63
0
Order By: Relevance
“…We and others previously showed that P-gp protein expression and transport activity are reduced in human A␤-overexpressing AD mouse models (Hartz et al, 2010;Mehta et al, 2013). These data are supported by studies with postmortem human brain tissue that demonstrate P-gp expression and activity levels are lower in the neurovasculature from patients with mild cognitive impairment and AD compared with those in age-matched, healthy individuals (Wijesuriya et al, 2010;Jeynes and Provias, 2011;van Assema et al, 2012;Deo et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We and others previously showed that P-gp protein expression and transport activity are reduced in human A␤-overexpressing AD mouse models (Hartz et al, 2010;Mehta et al, 2013). These data are supported by studies with postmortem human brain tissue that demonstrate P-gp expression and activity levels are lower in the neurovasculature from patients with mild cognitive impairment and AD compared with those in age-matched, healthy individuals (Wijesuriya et al, 2010;Jeynes and Provias, 2011;van Assema et al, 2012;Deo et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…Studies show that P-glycoprotein (P-gp), an efflux transporter in the luminal plasma membrane of brain capillaries, is critical for clearing A␤ from brain into blood (Lam et al, 2001;Cirrito et al, 2005;Kuhnke et al, 2007;Hartz et al, 2010). We and others showed that P-gp protein expression and transport activity levels are reduced in brain capillaries from AD mouse models, suggesting a link between high A␤ levels and reduced levels of brain capillary P-gp (Hartz et al, 2010;Mehta et al, 2013).…”
Section: Introductionmentioning
confidence: 91%
“…4 Since diazepam enters the brain by passive diffusion requiring neither a transporter nor energy, the measured brain uptake of [ 3 H]-diazepam depends on two factors: (1) infusion rate and (2) surface permeability. 13,14,25 Indeed, lipophilic solutes cross the BBB through a transcellular pathway, a process referred to as flow-limited transport. 9,14,28 However, a unique advantage of the in situ brain perfusion technique is to allow complete control on not only the perfusate content and perfusion time, but also the flow rate, by adjusting the pump.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models of AD (3xTg and Tg2576) have revealed a link between both Pglycoprotein 1 expression and activity in relation to disease progression (231,232). This evidence suggests that accumulation of the toxic form of Aβ can lead to downregulation of the P-glycoprotein 1 transporter.…”
Section: Atp-binding Cassette Transporter Familymentioning
confidence: 99%